Coumarin-transition metal complexes with biological activity: current trends and perspectives - Todorov, Lozan T.; Kostova, Irena P. (Frontiers in Chemistry, 2024)
Coumarin (2H-1-benzopyran-2-one) presents the fundamental structure of an enormous class of biologically active compounds of natural, semi-synthetic and synthetic origin. Extensive efforts are continually being put into research and development of coumarin derivatives with medicinal properties by the broad scientific community. Transition metal coordination compounds with potential biological activity are a "hot topic" in the modern search for novel drugs. Complexation with transition metals can enhance the physiological effect of a molecule, modify its safety profile and even imbue it with novel attributes of interest in the field of medicine and pharmacy. The present review aims to inform the reader on the latest developments in the search for coumarin transition metal complexes with biological activity, their potential applications and structure-activity relationships, where such can be elucidated. Each section of the present review would address a certain kind of biological activity (antiproliferative, antioxidant, antimicrobial, etc.), explore the most recent discoveries in the field and at the same time try to offer useful perspective for potential future investigations.